2017
DOI: 10.1039/c7ra08319j
|View full text |Cite
|
Sign up to set email alerts
|

Collagen modified with epoxidized safrole for improving antibacterial activity

Abstract: An epoxidized safrole, 5-(oxiran-2-ylmethyl)-benzo [d] [1,3]dioxole (OYBD), was synthesized and employed to modify collagen for improving its antibacterial activity. The interaction between collagen and OYBD, and the structure/properties of the modified collagen were investigated in detail. The results indicated that the OYBD-modified collagen showed a higher de-nature temperature (Td, 90.2 C), improved hydrophobic properties (contact angle from 84.2 to 89.1 ) and enhanced tensile strength (6.2-11.0%) without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Hence, the incorporation of an antibacterial effect in Col further contributes to its physicochemical characteristics. Col can be integrated with silver nanoparticles (AgNP) [ 63 ], collagencin [ 64 ], epoxidized safrole [ 65 ], polyhexamethylene biguanide [ 66 ], titanium dioxide [ 67 ], etc. Similarly, native gelatin does not show any antibacterial effect.…”
Section: Differences Between Collagen and Gelatinmentioning
confidence: 99%
“…Hence, the incorporation of an antibacterial effect in Col further contributes to its physicochemical characteristics. Col can be integrated with silver nanoparticles (AgNP) [ 63 ], collagencin [ 64 ], epoxidized safrole [ 65 ], polyhexamethylene biguanide [ 66 ], titanium dioxide [ 67 ], etc. Similarly, native gelatin does not show any antibacterial effect.…”
Section: Differences Between Collagen and Gelatinmentioning
confidence: 99%
“…Furthermore, increased mechanical and thermal collagen-properties without functionality loss were reported. Therefore, OYBD showed strong potential as a novel modifier for the development of antibacterial collagen-based biomaterials [ 252 ]. Apart from that, isolated safrole from Ocotea odorifera EO was recently found to possess remarkable antibacterial and antibiotic-modulating properties against multi-resistant efflux pump (EP)-carrying strains.…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…Additionally, DDSA‐collagen gels showed antibacterial properties mainly against Gram‐positive bacteria due to the increased hydrophobicity which is believed to be favorable in preventing water and bacteria intrusion for collagen‐based biomaterials (Xu et al, ). It has also been demonstrated that pathogenic bacteria and fungi have hydrophobic characteristics that make them irreversibly bind strongly to hydrophobic wound dressings by a physical principle (Ljungh, Yanagisawa, & Wadström, ).…”
Section: Discussionmentioning
confidence: 99%